Correlative cryo-fluorescence and cryo-scanning electron microscopy as a straightforward tool to study host-pathogen interactions - Strnad, Martin; Elsterová, Jana; Schrenková, Jana; Vancová, Marie; Rego, Ryan O M; Grubhoffer, Libor; Nebesářová, Jana (Scientific reports, 2015)
Correlative light and electron microscopy is an imaging technique that enables identification and targeting of fluorescently tagged structures with subsequent imaging at near-to-nanometer resolution. We established a novel correlative cryo-fluorescence microscopy and cryo-scanning electron microscopy workflow, which enables imaging of the studied object of interest very close to its natural state, devoid of artifacts caused for instance by slow chemical fixation. This system was tested by investigating the interaction of the zoonotic bacterium Borrelia burgdorferi with two mammalian cell lines of neural origin in order to broaden our knowledge about the cell-association mechanisms that precedes the entry of the bacteria into the cell. This method appears to be an unprecedentedly fast (<3 hours), straightforward, and reliable solution to study the finer details of pathogen-host cell interactions and provides important insights into the complex and dynamic relationship between a pathogen and a host.
Keywords: fluorescence; interakce hostitele a patogenu; Cell Line; Humans; elektronová kryomikroskopie; lidé; Borrelia burgdorferi; buněčné linie; mikroskopie elektronová rastrovací; Fluorescence; Host-Pathogen Interactions; Microscopy, Fluorescence; Microscopy, Electron, Scanning; fluorescenční mikroskopie; Cryoelectron Microscopy